Data mining methods for prediction of air pollution - Siwek, Krzysztof; Osowski, Stanisław (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses methods of data mining for prediction of air pollution. Two tasks in such a problem are important: generation and selection of the prognostic features, and the final prognostic system of the pollution for the next day. An advanced set of features, created on the basis of the atmospheric parameters, is proposed. This set is subject to analysis and selection of the most important features from the prediction point of view.
Keywords: computational intelligence; feature selection; neural networks; random forest; air pollution forecasting